Maternal smoking in successive pregnancies and recurrence of low birthweight: the 2004 Pelotas birth cohort study, Brazil Tabaquismo materno en sucesivas gestaciones y recurrencia de bajo peso al nacer: cohorte de nacimientos de Pelotas, Río Grande do Sul, Brasil, 2004 Tabagismo materno em sucessivas gestações e recorrência de baixo peso ao nascer: coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 2004 - Iândora Krolow Timm Sclowitz; Iná S. Santos; Marlos Rodrigues Domingues; Alicia Matijasevich; Aluísio J. D. Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
To evaluate the frequency of maternal smoking in successive pregnancies and its association with repetition of low birthweight, a study was conducted of a subsample of mothers from the 2004 Pelotas Birth Cohort in Brazil. Only women with previous histories of low birthweight newborns were included. Women with ≥ 2 previous births were eligible only if at least one of the two births immediately preceding the 2004 birth had low birthweight. From 4,458 births, 565 were included in this study. Frequency of smoking was 32.4%. Considering past pregnancies, 67.1% of mothers never smoked, 21.4% smoked during all pregnancies, 6.5% were ex-smokers, and 5% smoked only during the current pregnancy. In the adjusted analyses, when compared to mothers who never smoked, those who smoked during all pregnancies had 2.5 times greater probability of low birthweight recurrence in 2004 (PR = 2.5; 95%CI: 1.32-4.80). Smoking persistence is an important factor for the recurrence of low birthweight in successive pregnancies. Este estudio fue realizado en una submuestra de madres de la cohorte de nacimientos de Pelotas, Río Grande do Sul, Brasil, de 2004 para evaluar la frecuencia y asociación del tabaquismo en sucesivas gestaciones con el fenómeno de repetición del bajo peso al nacer. Se incluyeron solamente mujeres con antecedentes en el historial médico de recién nacidos con bajo peso al nacer. Se elegían a mujeres con ≥ 2 partos anteriores, solamente, si por lo menos uno de los dos partos inmediatamente anteriores al de 2004 hubiera sido de bajo peso al nacer. De los 4.458 nacimientos, 565 fueron incluidos en la muestra. La frecuencia de tabaquismo fue de un 32,4% y, teniendo en consideración las gestaciones anteriores, un 67,1% nunca fumaron; un 21,4% siempre fumaron; un 6,5% eran ex-fumadoras; y un 5,0% fumaron solamente en la gestación actual. En el análisis multivariable, las madres que fumaron en todas las gestaciones tuvieron una probabilidad 2,5 veces mayor de recurrencia de bajo peso al nacer en 2004, en comparación con las que nunca fumaron (RP = 2,5; IC95%: 1,32-4,80). La persistencia del tabaquismo es un factor importante para la recurrencia del bajo peso al nacer en sucesivas gestaciones. Este estudo foi realizado em uma subamostra de mães da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, de 2004, para avaliar a frequência e associação do tabagismo em sucessivas gestações com repetição de baixo peso ao nascer. Foram incluídas somente mulheres com história pregressa de recém-nascido com baixo peso ao nascer. Mulheres com ≥ 2 partos anteriores eram elegíveis somente se, pelo menos, um dos dois partos imediatamente anteriores ao de 2004 tivesse sido de baixo peso ao nascer. Dos 4.458 nascimentos, 565 foram incluídos. A frequência de tabagismo foi de 32,4%; e, levando em conta as gestações anteriores, 67,1% nunca fumaram; 21,4% sempre fumaram; 6,5% eram ex-fumantes; e 5% fumaram somente na gestação atual. Na análise multivariável, as mães que fumaram em todas as gestações tiveram uma probabilidade 2,5 vezes maior de recorrência de baixo peso ao nascer em 2004, em comparação às que nunca fumaram (RP = 2,5; IC95%: 1,32-4,80). A persistência do tabagismo é um importante fator para a recorrência do baixo peso ao nascer em sucessivas gestações.